PREPARATION OF CANDIDATE OF SOYBEANS IN-HOUSE REFERENCE MATERIALS FOR THE DETERMINATION OF CA, MG, FE, ZN, CU, AND PB BY ATOMIC ABSORPTION SPECTROPHOTOMETRY - RIZKI AMALIAH (NIM : 10508011); Pembimbing : Prof. Dr. Buchari, NUR
Reference material is a material that have certain properties, quite homogeneous and stable, which has been established with certainty to be used in the measurement process. There is two type of reference material, namely standard reference material and reference material with matrix. Currently, reference material with matrix is necessary for the purposes of analysis of a sample including food samples, but available amount is limited and high cost. This study aims to prepare candidates of soybean in-house reference materials for the determination of Ca, Mg, Fe, Zn, Cu, and Pb by atomic absorption spectrophotometry. Samples of soybean is obtained from supermarket in Bandung. The analysis performed included moisture, ash, and metal content. A method for determination of moisture, ash and metals was validated. Validation of method include limit of detection, linearity, homogeinity, stability, and precision. Analysis of moisture and ash were carried out by gravimetric method. Analysis on soybean samples for water, ash, and moisture content resulted μ (adb) = (5,73 Ã‚Â± 0,519)%, μ (adk) = (6,08 Ã‚Â± 0,530)% and ash content μ = (5,216 Ã‚Â± 0,220)%. The analysis of metal was determined using atomic absorption spectrophotometer from the ashes of destruction of the sample with a strong acid. Metal content in five samples of soy were μ = (12,7 Ã‚Â± 0,21) mg Ca, μ = (3,63 Ã‚Â± 0,12) mg Mg, μ = (0,155 Ã‚Â± 0,010) mg Fe, μ = (0,073 Ã‚Â± 0,006) mg Zn, μ = (0,029 Ã‚Â± 0,002) mg Cu, and μ = (0,002 Ã‚Â± 0,002) Pb.